The Effect of Cs-Controlled Triple-Cation Perovskite on Improving the Sensing Performance of Deep-Ultraviolet Photodetectors - Jun Seo Kim; Sangmo Kim; Hyung Wook Choi (Applied Sciences, 2025)
In this study, a UVC photodetector (PD) was fabricated by incorporating CsI into a conventional double-cation perovskite (FAMAPbI3) to enhance its stability. The device utilized a methylammonium iodide post-treatment solution to fabricate CsFAMAPbI3 perovskite thin films, which functioned as the primary light-absorbing layer in an NIP structure composed of n-type SnO2 and p-type spiro-OMeTAD. Perovskite films were fabricated and analyzed as a function of the Cs concentration to optimize the Cs content. The results demonstrated that Cs doping improved the crystallinity and phase stability of the films, leading to their enhanced electron mobility and photodetection performance. The UVC PD with an optimum Cs concentration exhibited a responsivity of 58.2 mA/W and a detectivity of 3.52 × 1014 Jones, representing an approximately 7% improvement over conventional structures.